Extracellular matrix stiffness regulates the proliferation and migration capacities of lymphatic endothelial cells via FAT1 - Xu, Zhangrun; Yu, Jian; Chen, Dandan; Liu, Yiwen; Zhang, Guoliang; Guo, Qian; Yang, Cuixia; Gao, Feng; He, Yiqing; Du, Yan (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe extracellular matrix (ECM) stiffness serves as a critical biomechanical regulator of cellular behavior. However, its specific roles on lymphatic endothelial cells (LECs) remains poorly characterized, particularly in the context of tumorigenesis where progressive matrix stiffening is a hallmark of the tumor microenvironments (TME).MethodsThe effects of ECM stiffness on LEC proliferation and migration were assessed using a tunable polyacrylamide hydrogel system. Differential gene expression in LECs on soft versus stiff substrates was identified by RNA-seq. To evaluate the stiffness-dependent regulation of FAT1 and its downstream mechanisms, we performed RT-qPCR, Western blot, immunofluorescence, wound healing, and spheroid assays. Furthermore, immunofluorescence was also used to compare FAT1 expression in tumor-associated versus normal lymphatic vessels.ResultsIn this study, we demonstrated that ECM stiffening significantly promotes LEC proliferation and migration. Notably, we observed marked downregulation of FAT1 expression in LECs cultured on tumor stiffness-mimicking matrix, a finding validated in clinical breast cancer specimens and murine models of breast cancer and melanoma. Mechanistic investigations identified FAT1 as a pivotal mechanotransducer that orchestrates LECs functional responses to biomechanical cues. Specifically, the knockdown of FAT1 facilitated β-catenin nuclear translocation, activating transcription of cell cycle regulators Myc and Cyclin D1 to coordinately promote LEC proliferation. Furthermore, FAT1 deficiency increased LEC mechanosensitivity by modulating focal adhesion formation, inducing cytoskeleton reorganization and consequent enhancement of migratory potentials.DiscussionTogether, our study uncovers FAT1 as a pivotal mechanosensor in LECs and highlight its significance in the biomechanical regulation. Targeting the FAT1-mediated signaling pathways may serve as a novel therapeutic strategy to inhibit tumor lymphatic metastasis.